2021
DOI: 10.1210/clinem/dgab578
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Glucagon-like Peptide-1 Receptor Agonists for the Management of NAFLD

Abstract: Context The burden of cirrhosis from NAFLD is reaching epidemic proportions in the United States. This calls for greater awareness among endocrinologists, who often see but may miss the diagnosis in adults with obesity or type 2 diabetes mellitus (T2D) who are at the highest risk. At the same time, recent studies suggest that GLP-1RAs are beneficial versus steatohepatitis (NASH) in this population. This minireview aims to assist endocrinologists to recognize the condition and recent work on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 86 publications
(121 reference statements)
3
55
0
3
Order By: Relevance
“…As GLP1 receptors are not present in the hepatocytes, it is generally agreed that GLP1 receptor agonists exert these beneficial effects indirectly through weight loss with alleviation of adipose tissue dysfunction and lipotoxicity, modulation of portal and peripheral plasma insulin and glucagon levels, as well as improvement in hepatocyte mitochondrial function and hepatic insulin resistance 89 .…”
Section: Incretin‐based Therapymentioning
confidence: 99%
“…As GLP1 receptors are not present in the hepatocytes, it is generally agreed that GLP1 receptor agonists exert these beneficial effects indirectly through weight loss with alleviation of adipose tissue dysfunction and lipotoxicity, modulation of portal and peripheral plasma insulin and glucagon levels, as well as improvement in hepatocyte mitochondrial function and hepatic insulin resistance 89 .…”
Section: Incretin‐based Therapymentioning
confidence: 99%
“…In recent years, the role of GLP-1RAs in NAFLD has also been investigated. The role of GLP-1RAs in hepatic steatosis and NASH is demonstrated in the previous studies ( 15 , 16 , 18 ). In contrast, its role in liver fibrosis in NAFLD is still controversial.…”
Section: Discussionmentioning
confidence: 55%
“…They are also effective in reducing both body weight and visceral adipose tissue, and have beneficial effects on the risk of cardiovascular and renal outcomes ( 9 13 ). In addition, recent evidence has shown that GLP-1RAs also improve hepatic histological components of NAFLD ( 14 16 ). Liraglutide and semaglutide consistently resolved NASH histologically in 40% to 60% of patients ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reports suggest that patients with NASH have impaired GLP-1 secretion ( 69 ); it strengthens the proposition of GLP-1 receptor agonists as a therapeutic option for management of NASH. Various GLP-1 receptor agonists like liraglutide, dulaglutide, semaglutide have shown to improve the pathogenesis of NASH ( 70 ). Tirzepatide, a dual agonist of GLP-1 and GIP has been found to improve various NASH-biomarkers in patients with type 2 diabetes ( 71 ).…”
Section: Non-alcoholic Steatohepatitis (Nash)mentioning
confidence: 99%